Application of Aquatic Chemical Analysis to Optimize Water Quality Management for Lobster Farming Productivity - Nudia Tuljannah; Afifah Nur Fadhilah; Kartini J; Risqah Amaliah Kasman; Dewi Hartini; Syamsul; Hasrul; Muh. Fauzan (ITEKES Permata Ilmu Maros, 2026)
Water quality is a critical factor in lobster farming, as aquatic conditions are closely associated with the health, growth, survival, and productivity of cultured organisms. An adequate understanding of water quality parameters is therefore essential to enable farmers to identify changes in aquatic conditions and implement appropriate management practices. This community service activity aimed to improve participants’ knowledge and understanding of aquatic chemical analysis and its application to water quality management to support lobster farming productivity. The activity was conducted at the Kurnia Baku People’s Hatchery Unit (UPR), Lekopancing Village, Tanralili District, Maros Regency, involving 20 participants. The activity was implemented through a counseling program comprising material presentation, discussions, question-and-answer sessions, and evaluation using pre-tests and post-tests. The materials covered an introduction to water quality, pH, dissolved oxygen (DO), ammonia, temperature, the importance of routine water quality monitoring, and appropriate management practices for maintaining suitable aquaculture conditions. The evaluation results demonstrated an improvement in participants’ understanding following the activity. The mean pre-test score increased from 58.5% to 85.5% in the post-test, representing an increase of 27 percentage points or 46.15% relative to the initial score. This improvement indicates that the counseling activity effectively enhanced participants’ understanding of the importance of aquatic chemical analysis as a basis for water quality management. The activity is expected to increase farmers’ awareness of the importance of routine water quality monitoring, thereby enabling better management of aquaculture environmental conditions and supporting sustainable lobster farming productivit